Design of Arterial Blood Pressure, Heart Rate Variability, and Breathing Rate Monitoring Device - Singh, Kalsi Mastan (My University, 2009)
An infrared emitter and a photodiode pressed against a highly vascular surface of a finger or on the brachial artery allow the photodiode to generate a current based on the infrared light it receives. Moreover, the varying amount of blood in the artery as the pulse passes through it impacts the light intensity the photodiode receives. Therefore, the signal received from the photodiode can be used to calculate the instantaneous heart rate and consequently the heart rate variability. Furthermore, the signal received from the photodiode is the photoplethysmographic (PPG) waveform which can be used to calculate the pulse transit time (PTT), the pulse height, and the breathing rate. PTT is the time interval between a peak on the finger PPG waveform and the corresponding peak on the brachial artery PPG waveform. Since PTT is inversely related to blood pressure changes, and the pulse height is proportional to the difference between the systolic and the diastolic pressure in the arteries, with correlation coefficients calculated with the aid of a standard blood pressure monitoring system, arterial blood pressure values can be calculated. By comparing the theories encompassing the hardware design with the experimental results the report articulates the effectiveness of the device.
Keywords: arterial blood pressure; brachial artery; breathing rate; heart rate variability; photodiode; photoplethysmographic; PPG; PTT; pulse height; systolic and diastolic pressure; Biomedical; Electrical and Computer Engineering; Biomedical